Effect of surface conductivity on electromagnetic shielding of multi-walled carbon nanotubes/Poly(ε-caprolactone) composites. (20th October 2022) - Tao, Jun-Ru; Tang, Xiao-Hong; He, Qian-Ming; Wang, Ming
Abstract: Herein, the effect of surface conductivity on microwave shielding effectiveness (SE) is discussed in the sandwiched multi-walled carbon nanotubes/poly(ε-caprolactone) (MWCNT/PCL) composites. The electrical conductivity on single or double-side surface of the composites is regulated by controlling different MWCNT loadings on the surface. The electromagnetic SE values of the MWCNT/PCL composites decrease with decreasing surface conductivity, and decline acutely when the surface becomes non-conductive. The shielding mechanism is investigated by a simulation and experimental study for the composites having different surface conductivity. The results indicate that the microwave reflection is very important to contribute the shielding performance of the composites. In addition, the effect of dielectric properties of surface layers on electromagnetic shielding performance was discussed for the composites with insulation surface. The composites with different polymers as insulting surface layers exhibit the close SE values, suggesting that the microwave shielding performance of the In/Con/In composites is irrelevant to the different polymer with different dielectric constant on the surface layers. Furthermore, the conductive network on surface exerts a great influence on microwave attenuation because of the enhancement on surface conduction loss and polarization loss. Therefore, the surface conductivity is a non-negligible factor for designing materials with excellent microwave shielding performance. Graphical abstract: The microwave shielding performance of conductive polymer composites is much dependent on the surface conductivity and increases with the increase of surface conductivity. Image 1 Highlights: Surface conductivity is very important to microwave shielding performance. EMI SE declines when one-side or double-side surface becomes insulation. Reduction of EMI SE is also found by a simulation study. Composites with different insulting surface polymers have close EMI SE values.